1984
DOI: 10.1111/j.1600-0722.1984.tb00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Initial corrosion of amalgams in vitro

Abstract: – The amounts of copper, mercury, silver or zinc released from two brands of freshly prepared, lathe cut amalgams and from one brand of dispersed phase type amalgam into artificial saliva have been measured. Samples were immersed in the solution a few minutes after the end of trituration and exposed statically for periods of up to about 4 days. The initial mercury release from such specimens could exceed the long term mercury release from old amalgams by more than two orders of magnitude. The measurements ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Mercury is released as metallic vapor (Gay et al, 1979;Mayer, 1980;Svare et al, 1981;Vimy and Lorscheider, 1985;Patterson et al, 1985), ions (Brune, 1981;Brune et al, 1983;Brune and Evje, 1984;Moberg, 1985), and particles (Brune, 1981;Her0 et al, 1983) from amalgam, but the absolute or even relative amounts are insufficiently explored for the various types of amalgam to deduce which amalgams would contribute most to the urine mercury level. In the present study, too few of the participants had all their restorations made of only one type of amalgam to make any comparison between the types of amalgam in relation to their effect on urine mercury level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mercury is released as metallic vapor (Gay et al, 1979;Mayer, 1980;Svare et al, 1981;Vimy and Lorscheider, 1985;Patterson et al, 1985), ions (Brune, 1981;Brune et al, 1983;Brune and Evje, 1984;Moberg, 1985), and particles (Brune, 1981;Her0 et al, 1983) from amalgam, but the absolute or even relative amounts are insufficiently explored for the various types of amalgam to deduce which amalgams would contribute most to the urine mercury level. In the present study, too few of the participants had all their restorations made of only one type of amalgam to make any comparison between the types of amalgam in relation to their effect on urine mercury level.…”
Section: Discussionmentioning
confidence: 99%
“…Dental amalgams release small amounts of mercury in the form of metallic vapor (Gay et al, 1979;Mayer, 1980;Svare et al, 1981;Vimy and Lorscheider, 1985;Patterson et al, 1985) and ions (Brune, 1981;Brune et al, 1983;Brune and Evje, 1984) and in particulate matter (Brune, 1981;Her0 et al, 1983). Several authors have examined to what extent such release contributes to the total body burden of mercury, by relating the blood and/or the urine content of Hg to the amount of dental amalgam restorations (Kr6ncke et al, 1980;Ott et al, 1984;Abraham et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous laboratory studies of mercury dissolution into solutions simulating the oral liquids have been reported (Babendererde et al, 1970;Oyama, 1974;Kawahara et al, 1976Kawahara et al, , 1979Kawahara et al, , 1981Takahashi et al, 1981;Kozono et al, 1982;Brune et al, 1983;Habu et al, 1983;Hero et al, 1983;Ohta, 1983;Brune and Evje, 1984;Brune, 1985;Brune and Evje, 1985;Ferracane et al, 1986;Ahmad and Stannard, 1987;Chung et al, 1987;Marek, 1987;Okabe et al, 1987;Ferracane et al, 1988a;Marek, 1988). The summarized results of some of these studies (Okabe et al, 1987) show an extremely wide range of the reported rates of the release.…”
Section: Introductionmentioning
confidence: 99%
“…These elements are those most commonly reported to occur in amalgam corrosion products (22). However, under the current experimental conditions the quantity of copper released from the specimens in NaCl was small or below the detection limit, ,and could not be related to the charge transfer.…”
Section: Discussionmentioning
confidence: 55%